Comprehensive identification of medication‐related problems occurring prior to, during and after emergency department presentation: An Australian multicentre, prospective, observational study. (22nd January 2020) - Taylor, Simone E; Mitri, Elise A; Harding, Andrew M; Taylor, David McD; Weeks, Adrian; Abbott, Leonie; Lambros, Pani; Lawrence, Dona; Strumpman, Dana; Senturk‐Raif, Reyhan; Louey, Stephen; Crisp, Hamish; et al.
Abstract: Objective: Patients present to EDs with various medication‐related problems (MRPs). MRPs are also associated with ED care, occurring during ED presentation or shortly afterwards. The aim of the present study is to describe the prevalence and nature of MRPs that occur prior to, during or shortly after leaving ED. Methods: We undertook a prospective, observational study in nine Australian EDs. Blocks of 10 consecutive adult patients who were not seen by a pharmacist in ED and who presented at pre‐specified times were identified. Within 1 week of ED discharge, a pharmacist interviewed patients and undertook a medical record review to determine their medication history, patients' understanding of treatment, potential MRP risk factors and manage any identified MRPs. Results: A total of 904 patients were recruited: 14.8% aged ≥80 years, 18.9% taking more than eight regular medications; 581 MRPs were identified; 287 (49.4%, 95% confidence interval [CI] 45.3–53.5%) of moderate‐high significance. Most highly significant MRPs involved high‐risk medications, particularly strong opioids, insulin and anti‐coagulants. The most common types of MRPs were prescribing errors (46.8%), patient adherence/knowledge issues (31.2%) and adverse drug reactions (7.4%). Of all patients, 381 (42.1%, 95% CI 38.9–45.5%) had at least one MRP; 31.4% (95% CI 28.4–34.6%) had MRPs that could be identified or managed by screening at ED presentation and 12.4% (95% CI 10.4–14.8%) had MRPs that could be identified or managed by screening at ED discharge. Conclusions: Patients experienced a range of MRPs throughout the ED continuum of care. From these data, screening tools will be developed so that ED clinicians may identify patients at greatest risk of MRPs.